Banana Leaf Meal, A Tamil Traditional Way of Eating - Menaka, S. (University of Sri Jayewardenepura, 2020)
Leaves are the prime plates to serve food since the time human lived in forests. Serving food on banana leaves is a long standing Tamil culinary tradition especially in Sri Lanka and South India. Following the traditions serve as an avenue for creating lasting memories of the families. The study was conducted with the objective of studying the value of banana leaf meal in Jaffna district. Data collection was made via interview and discussion from the local elders Thenmaradchi area. Visits were made to the food corners and banquet halls to observe the use of banana leaves for serving foods. Banana leaves are used to serve vegetarian foods in temple festivals, family functions and religious functions. Fresh banana leaves are considered as more sterile during fasting periods. The leaves are thick, large and flexible to accommodate multicourse Hindu meal and liquid dishes. The leaves cannot be punctured and they are waterproof. When a hot food served on the leaf, it imparts unique flavour and polyphenols, which are the natural antioxidants on the leaves, are activated. The eco friendly, non-sticky leaves are free from detergents and the used leaves can be given as livestock feed. The traditional banana leaf meal is eaten with hands by sitting on the floor. The meal is still practised by Hindus in Friday lunch. Banana leaves play major role in offering food in Hindu temples, as they are clean and pure. A meal is generally served on a half leaf and full single leaf is used serve an important and respectable person in the family. Vegetarian food corners use the leaves to serve the customers and the leaves give livelihood for the banana cultivators. Eating on leaves is slowly disappearing with the buffet culture and busy life style. However, people like to follow the traditions and the leaves are cut to fit the dimension of the plate to serve food in banqueting halls. Having food on banana leaves are economical and the use of banana leaf was the backbone of Tamil cutlery. The tradition of eating food on banana leaf should be followed to build up a plastic free healthy nation.
Keywords: Banana leaf; Tamil Cuisine; traditional; Vegetarian; Hindu